A stable isotope perspective on archaeological agricultural variability and Neolithic experimentation in India. (May 2022) - Nayak, Ayushi; Basa, Kishor K.; Boivin, Nicole L.; Fuller, Dorian Q.; Mohanty, Rabindra K.; Kingwell-Banham, Eleanor; Murphy, Charlene; Roberts, Patrick J.; Lee-Thorp, Julia; Bogaard, Amy
Abstract: Agriculture has been crucial in sustaining human populations in South Asia across dramatically variable environments for millennia. Until recently, however, the origins of this mode of subsistence in India have been discussed in terms of population migration and crop introduction, with limited focus on how agricultural packages were formulated and utilised in local contexts. Here, we report the first measurements of stable carbon and nitrogen isotope values in well-preserved charred crop remains from sites spanning the Neolithic/Chalcolithic to the Early Historic in two very different environmental zones: tropical East India and the semi-arid Deccan. The results show that this approach offers direct insight into prehistoric crop management under contrasting environmental constraints. Our preliminary results plausibly suggest that early farmers in India experimented with and made strategic use of water and manure resources in accordance with specific crop requirements and under varying environmental constraints. We suggest that the development of modern crop isotope baselines across India, and the application of this methodology to archaeological assemblages, has the potential to yield detailed insight into agroecology in India's past. Highlights: First archaeobotanical stable isotope data from Neolithic/Chalcolithic peninsular India. Direct insight into crop management by early farmers. Early farmers strategically used water resources to tackle environmental constraints. Early farmers exploited dung and dung-ash as manure.